Healthcare Professionals’ Views of Factors Influencing Diabetes Self-Management and the Utility of a mHealth Application and Its Features to Support Self-Care - Yoon, Sungwon; Ng, Jun Hao; Kwan, Yu Heng; Low, Lian Leng (Frontiers in Endocrinology, 2022)
Introduction: The perspectives of healthcare professionals (HCPs) are pivotal to co-development of self-management strategies for patients with diabetes. However, literature has been largely limited to perspectives of patients within the context of a Western healthcare setting. This study aims to explore factors influencing diabetes self-management in adult patients with diabetes from the perspectives of HCPs and their views of the value of mHealth application for diabetes self-management. Materials and methods: We conducted focus group discussions (FGD) with purposively selected HCPs in Singapore. All FGDs were audio-recorded and transcribed verbatim. Thematic analysis was conducted using NVivo 12. Results: A total of 56 HCPs participated in the study. Barriers to self-management included limited patient commitment to lifestyle changes, suboptimal adherence to medication and treatment, patient resistance to insulin initiation and insufficient rapport between patients and HCPs. Patients’ perceived susceptibility to complications, social support from family and community, multidisciplinary team care and patient’s understanding of the benefits of self-care were viewed as facilitating self-management. HCPs saw mHealth apps as a vital opportunity to engage patients in the self-management of conditions and empower them to foster behavior changes. Yet, there were concerns regarding patient’s limited digital literacy, lack of integration into routine electronic system and reluctance. Discussion: We identified a set of factors influencing self-management in adult patients with diabetes and useful app features that can empower patients to manage their conditions. Findings will inform the development of a mHealth application, and its features designed to improve self-care.